Objective-C for iPhone developers [ a beginner's guide - Brannan, James A. (New York : McGraw-Hill, 2010)
"Shows you how to use the Objective-C programming language, Apple's Foundation framework, the iPhone SDK, and the Xcode development environment. ... Real-world examples throughout the book correspond with downloadable Ccode projects and video tutorials so you can get started with your first app right away."
1. Exploring the iPhone SDK and basic programming -- 2. Primitive data types and operators -- 3. Flow control statements, arrays, and structures -- 4. Classes, objects, and messaging -- 5. Memory management and properties -- 6. Inheritance -- 7. Protocols and categories -- 8. Some foundation framework classes -- 9. File handling -- 10. Property lists, NSCopy, and archiving -- 11. Selectors and targets -- 12. The model-view-controller design pattern
Includes index
Keywords: iPhone (Smartphone); Objective-C (Computer program language); Object-oriented programming (Computer science)